Atherosclerosis risk factors in women with coronary heart disease developed before the age of 65 years - N. V. Izmozherova; A. A. Popov (Российский кардиологический журнал, 2008)
The study aimed at assessing atherosclerosis risk factors in women with early (<65 years) development of coronary heart disease (CHD). This case?control study included 167 climacteric women with stable effort angina and 167 CHD-free females (controls). Anthropometry and lipid profile parameters, rates of arterial hypertension (AH), chronic heart failure, stroke, and depression were assessed. CHD was associated with higher rates of AH, abdominal obesity, Type 2 diabetes mellitus, depression, knee osteoarthrosis, low level of high-density lipoprotein cholesterol, and more severe climacteric syndrome. Women with CHD had higher odds of stroke and longterm disability. Percentage of females with higher education was greater in the controls. Conclusion: Early CHD development in women was associated with multiple atherosclerosis risk factors.